PPKn Teacher's Strategy in Overcoming Deviant Behavior of Students at SMPN 14 Sarolangun - Saputra, Epik; Nurdin, Buchari; Juliardi, Budi (CV. Rayyan Dwi Bharata, 2022)
This research is backgrounded by the problems, namely: How is the application of learning strategies by PPKn teachers in dealing with deviant behavior. The purpose of the study was to find out the strategies of PPKn teachers in overcoming deviant behavior, how the implementation of learning strategies by PPKn teachers, what obstacles were found by PPKn teachers in dealing with deviant behavior. The type of research used is qualitative research with descriptive methods, research informants are school principals, PPKn teachers, waka student affairs, waka curriculum, parents, and students who do deviant behavior at school. Data collection techniques used are observation, interview, and documentation techniques. Data processing with data analysis with data reduction steps, data display, and drawing conclusions verification. The results showed that the strategies of Civics teachers in dealing with deviant behavior were, providing classroom learning, delivering learning about norms in the life of society, nation and state. by taking preventive measures, giving sanctions to students who violate the rules, giving advice, and taking an intensive approach. In addition to being in the classroom, teachers can carry out activities outside the classroom, namely by placing themselves as friends for students, teachers can accept the outpouring of students who have problems so that they can provide input to students in finding solutions to their problems, teachers also direct students to behave positively according to with school rules and regulations.